Organotrifluoroborates and Monocoordinated Palladium Complexes as Catalysts—A Perfect Combination for Suzuki–Miyaura Coupling - Molander, Gary A. (2009)
Monocoordinated palladium catalysts derived from sterically hindered, electron-rich phosphines or N-heterocyclic carbenes have revolutionized the Suzuki–Miyaura coupling reaction. The emergence of organotrifluoroborates has provided important new perspectives for the organoboron component of these reactions. In combination, these two components prove to be extraordinarily powerful partners for cross-coupling reactions.